The role of markers of endothelial dysfunction, oxidative and cellular stress in the prediction of myocardial infarction in comorbid patients with stable coronary heart disease - Yuliya A. Kotova (Concilium Medicum, 2021)
Aim. To study the role of markers of endothelial dysfunction, oxidative and cellular stress in the prediction of myocardial infarction (MI) in comorbid patients with stable coronary heart disease (CHD).